Development of Android-Based Interactive Multimedia Non-Fiction Text Materials Containing Kediri Raya Local Wisdom and 4C Skills - Endang Sri Mujiwati; Kukuh Andri Aka; Rian Damariswara (Universitas Pendidikan Mandalika (UNDIKMA), 2022)
The study aims to create interactive multimedia non-fiction text material based on Android with the content of Kediri Raya local wisdom and 4C skills and assess the validity of the developed interactive multimedia. This study used is development research methods with ADDIE model. The research subjects were fourth-grade elementary school students. The research instrument used a questionnaire. Qualitative descriptive data analysis in this study was used to process data sourced from comments and suggestions from validators contained in the validation questionnaire. Quantitative descriptive data analysis was used to analyze the data obtained from expert and user validation. The results showed that (1) First, performance and needs analysis. Second, the determination of interactive multimedia designs that are attractive, easy to use, and in accordance with learning. Third, the development of non-fiction text material containing Kediri Raya local wisdom, the development of questions containing 4C skills, and the development of Android-based interactive multimedia. Fourth, implementation, which is implemented in SD. Before being implemented in SD, it must go through the validation of material and media experts. Fifth, evaluation, which contains values and inputs given by material and media experts, is the basis for improving interactive multimedia and (2) the results of material expert validation get a score of 85.7% and media expert validation gets 97%. The product can be used in learning Indonesian in 4th-grade elementary school as a solution for online learning.